The First Serological Study of Coxiella burnetii among Pregnant Women in Iran - Maryam KHAYYAT KHAMENEIE; Javad ASADI; Mohammad KHALILI; Zeinab ABIRI (Tehran University of Medical Sciences, 2016)
Background: Q fever is a zoonotic disease caused by Coxiella burnetii. There is no information about this disease in pregnant women in Iran. The aim of this study was to investigate the seroprevalence of C. burnetii infection among pregnant women in southwestern (Ahvaz) and northern (Parsabad) Iran and further to comparison its prevalence in normal and abnormal pregnancies. Methods: A total of 400 samples were collected randomly from pregnant women who referred to diagnostic laboratories of Ahvaz and Parsabad in 2014. An indirect ELISA kit, designed in Veterinary Faculty, was used to detect the specific antibodies against phase II humanC. burnetii in serum samples. Results: The overall prevalence of C. burnetii in sera from pregnant women was 29.3% (95% confidence interval (CI): 25-34%). The prevalence of C. burnetii infection was significantly different in Ahvaz and Parsabad with, respectively, 22 (95% CI: 16-28%) and 36.5% (95% CI: 30-43%). Total prevalence of C. burnetii infection in serum was significantly higher in women with abnormal pregnancy history (39.8%) compared with normal pregnancies (23.8%). Furthermore, maternal age had significant association with seropositivity and the prevalence increased with maternal age. This could be due to higher probability of encountering C. burnetii in older women. Conclusion: The present study demonstrated ahigh seroprevalence of C. burnetii infection among pregnant women in Iran for the first time. Seropositivity was associated with adverse pregnancy outcomes and maternal age. The pregnant women who experienced abnormal pregnancy had higher seroprevalence of C. burnetii compared to women with normal pregnancy.